Factors Influencing Teachers to Stay in The Profession Case of Albania - Agaj, Desara (European Journal of Multidisciplinary Studies, 2023)
Researchers show that exist many factors that influence teachers to remain in the profession. Legal changes happening in Albania during these years have brought some difficulties in the profession of a teacher, raising their workload and a lot of documents to fulfill that in some cases drain the teacher’s energy and limit their time to work with children. This article comes as a result of a previous study on searching for factors that influence teachers to choose their profession.The aim of this article is to study why teachers in Albania stay in their profession using semi-structured interviews with 68 (sixty-eight) teachers at different levels. The methodology used in this study consists of a qualitative design. This study highlighted some factors that influence teachers in Albania to stay in their profession such as internal factors (motivation, love for students, job satisfaction, working with children, etc.) and less external factors (sustainability in salary, financial stability, etc.).
Keywords: Teacher, profession, internal factors, external factors.